GAMBARAN TEKAN INTRAOKULAR PADA PEMAIN MUSIK BAMBU - Rampi, Chintya N (e-Biomedik, 2013)
ABSTRACT : Intraocular pressure (IOP) is an important measure because corelated with glaucoma that can lead to blindness if not prevented early. Factors affecting the intraocular pressure include gender, age, nationality, race, physiological differences such as high blood pressure and cardiovascular disease. Music is a product of human culture. One kind of music is a bamboo wind instrument that originated from Minahasa, comprised of flute, saxophone, Corno, trombone, tuba, bass, and trumpet. This study was aimed to reveal the IOP of a bamboo wind instrument players from Pinapalangkou village - South Minahasa. This was an observational cross sectional study. The research sample amounted to 31 people who have met the inclusion criteria, ie 15-83 years old, physically and mentally healthy while doing research, had been playing music for more than 1 year, willing to be sampled and signed informed consent. Measurement of IOP using a schiotz tonometer. Based on the results there were 31 male player, and at night inspection was found that there were 3 people (9.7%) had an increase of IOP and 28 people (90.3%) had normal IOP. There are 3 subjects from 31 studied subjects had an elevated intraocular pressure while 28 studied subjects had normal IOP. Keywords: intraocular pressure, Bamboo Music Players ABSTRAK: Tekanan intraokular merupakan ukuran yang penting karena berhubungan penyakit glaukoma yang dapat menyebabkan kebutaan jika tidak dicegah sejak dini. Faktor yang mempengaruhi tekanan intraokular adalah jenis kelamin, usia, bangsa, ras, perbedaaan fisiologis seperti darah tinggi dan kardiovaskular. Musik adalah produk kebudayaan manusia. Salah satunya musik tiup bambu yang berasal dari Minahasa. Terdiri dari seruling, saxophone, corno, trombone, tuba, bass, dan trompet. Penelitian ini bertujuan untuk mengetahui gambaran tekanan intraokular pada pemain musik tiup bambu di desa Pinapalangkou - Minahasa Selatan. Penelitian ini bersifat observasional, dengan rancangan cross sectional study. Sampel penelitian berjumlah 31 orang yang telah memenuhi kriteria inklusi yaitu berumur 15-83 tahun, sehat jasmani dan rohani saat dilakukan penelitian, lebih dari 1 tahun memainkan musik, bersedia dijadikan sampel penelitian dan menandatangani informed consent. Pengukuran tekanan intraokular mengunakan alat tonometer schiotz. Berdasarkan hasil penelitian terdapat 31 pemain pria, pemeriksaan pada malam hari didapatkan bahwa ada 3 orang (9,7%) mengalami peningkatan tekanan intraokular dan 28 orang (90,3%) memiliki tekanan intraokular dalam batas normal. Terdapat 3 subjek dari 31 subjek memiliki peningkatan tekanan intraokular sedangkan 28 subjek memiliki tekanan intraokular dalam batas normal. Kata kunci: Tekanan Intraokular,Pemain Musik Tiup Bambu